THE ISSUE OF INTERNAL DISPLACEMENT AND EMIGRATION OF THE ARMENIAN POPULATION OF VAN AND BITLIS PROVINCES OF WESTERN ARMENIA AT THE END OF XIX AND BEGINNING OF XX CENTURIES - Bablumyan, Arpine (Armenian Folia Anglistika, 2025)
The study of problems related to the demography of Western Armenia is highly topical, because it covers the real goals of the anti-Armenian policy of the Ottoman authorities. The main trends of population movements, which were recorded in the provinces of Van and Bitlis at the end of XIX and beginning of XX centuries are discussed within the framework of the article. Movements, both within the country and to adjacent or more distant areas, were common to the Armenians of almost all provinces of Western Armenia, but Van and Bitlis were characterized by certain commonalities, which were especially related to more insecure and poor condition of the population of these provinces, as well as referred to the main directions of movements: the main destinations of emigration from Van and Bitlis were to Eastern Armenia, other parts of the Russian Empire and Persia. The article also touches on the reasons of emigration and also the labor migration, such as - insecurity, persecution, violence, massacres, forced Islamization, and direct consequences: decrease of the number of the Armenian population, depopulation of Armenian settlements, etc. The study was carried out using a historical-comparative approach, supported by historical-demographic and content analysis methods.
Keywords: Western Armenia; Van; Bitlis (Baghesh); demography; emigration; hamidian massacres